Relevansi Anarki Epistemologis Paul Fayerabend Bagi Studi Agama - Taufik Ajuba (Farabi, 2016)
The development of science is a complex process of individual creativity. Because of that science should not be described or regulated by any form of regulation or legal system. To resist attempts to curb the science in formal and rigid forms, Paul Feyerabend offers two things, namely that replicates the principles and the principle of anything goes. The principle of the development means, we do not work in a system of thought life forms and the single institutional framework. Instead, we should put pluralism as a theory and methodology, systems of thought and forms of life within the institutional framework. And the principle of freedom anything goes (anything goes), means freeing all forms of a trip is, without much bound by a system. Feyerabend thought it quite well practiced in religious studies because they could create an understanding that is not stuck to the approach dogmatic and ideological. The plurality of approaches when assessing religions is richness to create a wide variety of religious studies approaches.